2023
DOI: 10.1108/ijchm-05-2023-0586
|View full text |Cite
|
Sign up to set email alerts
|

Metaverse in hospitality and tourism: a critical reflection

Lai-Wan Wong,
Garry Wei-Han Tan,
Keng-Boon Ooi
et al.

Abstract: Purpose This study aims to discuss the current context, scope and impacts of a metaverse in the hospitality and tourism industry. Although existing literature discussed the potentials of the metaverse in this context, the ways the metaverse work is still being defined and accessing a complete metaverse is still not yet possible. This existing knowledge will become increasingly sophisticated and complex as developments in the metaverse continue, eventually contributing to a knowledge gap in knowledge, and its i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…In order to answer this question, the study adopts an analytic approach consolidates insights derived from over 50 academic studies from leading journals at the intersection of heritage digitization and immersive tourism, including Tourism Management (Buhalis, Leung et al, 2023), International Journal of Tourism Cities (Zhang, J. and Quoquab, 2023), Tourism Review (Zhang, J., Quoquab et al, 2024), International Journal of Contemporary Hospitality Management (Wong, Tan et al, 2023), Information Technology and Tourism (Fazio, Fricano et al, 2023), and Current Issues in Tourism (Medai and Wu, 2023;Özdemir Uçgun and Şahin, 2023;Trunfio, Campana et al, 2020a), surfaced through scholarly databases like Web of Science, Scopus, and Google Scholar, along with relevant policy guidelines from agencies like UNESCO, UNWTO, ICOMOS, and EU on matters of digital ethics, community participation needs, and museum technology adoption protocols (EU, 2021;UNESCO, 2013, n.d.;UNWTO, 2013;Wei, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…In order to answer this question, the study adopts an analytic approach consolidates insights derived from over 50 academic studies from leading journals at the intersection of heritage digitization and immersive tourism, including Tourism Management (Buhalis, Leung et al, 2023), International Journal of Tourism Cities (Zhang, J. and Quoquab, 2023), Tourism Review (Zhang, J., Quoquab et al, 2024), International Journal of Contemporary Hospitality Management (Wong, Tan et al, 2023), Information Technology and Tourism (Fazio, Fricano et al, 2023), and Current Issues in Tourism (Medai and Wu, 2023;Özdemir Uçgun and Şahin, 2023;Trunfio, Campana et al, 2020a), surfaced through scholarly databases like Web of Science, Scopus, and Google Scholar, along with relevant policy guidelines from agencies like UNESCO, UNWTO, ICOMOS, and EU on matters of digital ethics, community participation needs, and museum technology adoption protocols (EU, 2021;UNESCO, 2013, n.d.;UNWTO, 2013;Wei, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…By creating immersive and interactive virtual environments, the Metaverse can enable tourists to remotely explore destinations, attractions, and events, overcoming the physical, temporal, and financial constraints they may face [15,16]. Moreover, the Metaverse can facilitate personalized and engaging experiences, allowing tourists to interact with virtual guides, avatars, and other users, all the while fostering social connections and cultural exchange [38][39][40].…”
Section: Literature Review 21 the Metaverse And Its Applications In T...mentioning
confidence: 99%
“…Interconnected digital twins: Creating a network of interconnected digital twins can not only enhance cultural heritage appreciation but also promote sustainable tourism and conservation efforts. These virtual platforms can serve as powerful tools for education, engagement, and research [39,40,[80][81][82].…”
mentioning
confidence: 99%
“…Previous research has analyzed how immersive technologies/virtual worlds (e.g., Yung et al, 2022) can be applied in the events industry. The metaverse is a technological revolution that provides highly immersive, social and interactive experiences that can, in a virtual setting, replicate and extend many aspects of in-person events (Dwivedi et al, 2022;Wong et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the novelty of the metaverse as a research concept, academic literature on its application to the customer experience is scarce (Dwivedi et al, 2023a). Existing research is mostly conceptual in nature (e.g., Buhalis et al, 2022Buhalis et al, , 2023Dwivedi et al, 2022;Go & Kang, 2023;Gursoy et al, 2022;Mladenović et al, 2023;Richter & Richter, 2023;Wong et al, 2023). Among the few empirical exceptions, in the tourism industry Tsai (2022) found that users' perceptions of holistic presence (spatial, social and self-presence) in the metaverse affected (directly and indirectly through holistic happiness) their behavioral intentions to visit a real destination.…”
Section: Introductionmentioning
confidence: 99%